2014
DOI: 10.1002/eji.201444798
|View full text |Cite
|
Sign up to set email alerts
|

microRNA management of NK‐cell developmental and functional programs

Abstract: Summary NK cells are innate lymphoid cells that are critical for host defense against infection, and mediate anti-tumor responses. MicroRNAs (miRNAs) are a large family of small non-coding RNAs that target the 3′UTR of mRNAs, thereby attenuating protein translation. The expression of miRNAs within human peripheral blood and mouse splenic NK cells has been cataloged, with the majority of the miRNA sequence pool represented in the top 60 most abundantly expressed miRNAs. Global miRNA deficiency within NK cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…In particular, miR-155 is a pleiotropic modulator of innate and adaptive immunity [1517], and might promote autoimmune inflammation [18]. Beside its role as tumor-suppressor [19], miR-16 was recently shown to affect NK function by repressing IFNγ expression [20], and to promote M1 pro-inflammatory type macrophage polarization, affecting T cell activation [21]. No data are instead available on miR-1238 potential functions in immunity, as it was so far recognized only as a tumor-suppressor factor [22].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-155 is a pleiotropic modulator of innate and adaptive immunity [1517], and might promote autoimmune inflammation [18]. Beside its role as tumor-suppressor [19], miR-16 was recently shown to affect NK function by repressing IFNγ expression [20], and to promote M1 pro-inflammatory type macrophage polarization, affecting T cell activation [21]. No data are instead available on miR-1238 potential functions in immunity, as it was so far recognized only as a tumor-suppressor factor [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice that are genetically altered to inhibit expression of both TBET and EOMES lack mature NK cells (22). Recently, microRNAs (miRs) have also emerged as important regulators of immune cell development and function (23)(24)(25)(26), and the modulation of TBET and EOMES has been linked to miR-29b in T cell studies (23,27). To date, the importance of miR regulation of NK cell development in the setting of cancer has not been evaluated.…”
Section: Cd56mentioning
confidence: 99%
“…Recent advances have demonstrated that miRNAs are crucial in NK cell biology [50] . For instance, miR150 and miR181 regulate NK cell development [51,52] .…”
Section: Mirnas and Nk Cellsmentioning
confidence: 99%